BAURAN PEMASARAN JAMBU KRISTAL DI BUMIAJI KOTA BATU - Farah Mutiara; Ninin Khoirunnisa (Universitas Islam Madura, 2021)
Marketing strategy has a very important role for the success of a company in general and in marketing in particular. Because considering the increasingly sophisticated times with increasingly varied technologies, making it easier for companies to increase their marketing. But besides that, the marketing strategy that is implemented must be reviewed and developed in accordance with market developments and the market environment. The objectives of this study were: To analyze the marketing channels of guava crystal fruit at UD. Bumiaji Sejahtera Desa Bumiaji Kec. Bumiaji Batu City. And Knowing the Partnership at UD. Bumiaji Sejahtera Desa Bumiaji Kec. Bumiaji Batu City. This research was conducted at UD Bumiaji Sejahtera, Bumiaji Village, Bumiaji District, Batu City in April 2020. The method of data analysis in this study used a descriptive approach. The results of this research are the marketing channels carried out by UD. Bumiaji Sejahtera, which is located in Bumiaji sub-district, Batu City, is arguably quite good, this can be seen from the 4 elements of marketing channels used by the company very optimally. As well as a suitable partnership to do UD. Bumiaji Sejahtera namely; cooperation with the producers of the Tour and Trevel. Batu City, which is known as a tourist city, is never empty of local and foreign tourists, so the Tour and Travel Producers will direct you to the location of UD. Bumiaji Sejahtera.